Paleoethnobotany as Ethnobotany as Paleoethnobotany. Issue Volume 43:Issues 1(2023) (March 2023) - Pearsall, Deborah M.
Paleoethnobotany and ethnobotany are closely intertwined. Ethnobotany provides a key interpretive framework for understanding past plant–people interrelationships through the archaeological record, and this understanding of the past provides the foundation for understanding present-day relationships between people and the natural world.